Student Violation Point Information System Using The Web-Based Waterfall Method - Dani Dani; Reza Saputra; A Nurul Anwar (bit-Tech, 2025)
Juvenile delinquency remains a growing concern in school environments, where ineffective manual documentation often slows disciplinary decision-making and delays communication with parents. This study aims to design and develop a web-based student violation information system that integrates WhatsApp notifications to support real-time parental engagement. Using the Waterfall methodology, the system was built with PHP and MySQL and evaluated in a school setting involving administrators, teachers, and parents as primary users. The analysis stage identified recurring inefficiencies in existing disciplinary workflows, including incomplete records and an average communication delay of two to three days between violation occurrence and parental notification. The developed system streamlines these processes by enabling structured data entry, automated point calculation, and instantaneous message delivery. Functional testing across twelve core features showed 100% alignment between expected and actual outputs, while user feedback from initial deployment indicated faster access to violation records and improved traceability of student behavior. Preliminary observations also suggested a reduction in documentation time, from approximately five minutes per case to under two minutes. These findings demonstrate the system’s potential to enhance accuracy, accelerate information flow, and strengthen disciplinary governance within schools. The implications highlight the value of integrating real-time communication technologies into school information systems to support timely intervention and increased parental involvement. Overall, this study provides an empirically grounded model that can be adapted by educational institutions seeking more transparent, efficient, and accountable mechanisms for managing student violations.